2022
DOI: 10.1136/jim-2021-002224
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of complement factors in severely ill patients with COVID-19

Abstract: Coagulopathy, cytokine release, platelet hyperactivity and endothelial activation are regarded as potential major contributors to COVID-19 morbidity. Complement activation might provide a bridge linking these factors in severe COVID-19 illness. In this study, we investigated the prognostic significance of selected complement factors in hospitalized patients with severe COVID-19 infection. The study included 300 hospitalized adults with severe COVID-19 infection. Complement factors (C3, C3a, C4, sC5b-9) were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…To the Editor, We recently have read with great interest the article written by Dr. Hassan et al published in October 2022 issue of Journal of Investigative Medicine. 1 The authors measured the serum levels of complement factors in hospitalized patients with severe course of coronavirus disease 2019 (COVID-19). The study showed that survivors had significantly higher C3 and C4 levels and lower levels of complement activation products, C3a and sC5b-9, and provided strong evidence on prognostic value of these complement factors for mortality.…”
mentioning
confidence: 99%
“…To the Editor, We recently have read with great interest the article written by Dr. Hassan et al published in October 2022 issue of Journal of Investigative Medicine. 1 The authors measured the serum levels of complement factors in hospitalized patients with severe course of coronavirus disease 2019 (COVID-19). The study showed that survivors had significantly higher C3 and C4 levels and lower levels of complement activation products, C3a and sC5b-9, and provided strong evidence on prognostic value of these complement factors for mortality.…”
mentioning
confidence: 99%